Computational Science and Its Applications - ICCSA 2014 14th International Conference, Guimarães, Portugal, June 30 - July 3, 204, Proceedings, Part VI - Murgante, Beniamino; Misra, Sanjay; Rocha, Ana Maria Alves Coutinho; Torre, Carmelo; Rocha, Jorge Gustavo; Falcão, Maria Irene; Taniar, David; Apduhan, Bernady O.; Gervasi, Osvaldo (Theoretical Computer Science and General Issues,, 2014)
The six-volume set LNCS 8579-8584 constitutes the refereed proceedings of the 14th International Conference on Computational Science and Its Applications, ICCSA 2014, held in Guimarães, Portugal, in June/July 2014. The 347 revised papers presented in 30 workshops and a special track were carefully reviewed and selected from 1167. The 289 papers presented in the workshops cover various areas in computational science ranging from computational science technologies to specific areas of computational science such as computational geometry and security.